(untitled) (East West Medical College Journal, 2025)
Background: Dengue is an endemic infection in Bangladesh with frequent outbreaks. Dengue shock syndrome (DSS) contributes to the majority of mortality in dengue infection. Neutrophil-lymphocyte ratio (NLR) was found as a predictor of severe dengue in a recent study. Objective: This study was conducted to assess the association of NLR and the development of DSS. Methods: This case-control study was conducted on 42 dengue patients admitted under the Department of Medicine of Shaheed Monsur Ali Medical College Hospital from July to October 2023. Association of NLR on the third day of fever with DSS was assessed following appropriate statistical procedures. Results: Mean NLR on the third day of fever was higher in DSS patients. NLR≥2 was associated with a statistically significant higher proportion of DSS. Conclusion: An NLR≥2 on the third day of fever possesses a higher risk of developing DSS. These patients should have close monitoring and be discharged from the hospital after complete recovery. EWMCJ Vol. 13, No. 1, January 2025: 50-53